2017
DOI: 10.1111/oik.03661
|View full text |Cite
|
Sign up to set email alerts
|

Explaining ecological shifts: the roles of temperature and primary production in the long‐term dynamics of benthic faunal composition

Abstract: Predicting the ecological consequences of environmental change requires that we can identify the drivers of long‐term ecological variation. Biological assemblages can exhibit abrupt deviations from temporal trends, potentially resulting in irreversible shifts in species composition over short periods of time. Such dynamics are hypothesised to occur as gradual forcing eventually causes biological thresholds to be crossed, but could also be explained by biota simply tracking abrupt changes to their environment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 72 publications
0
9
0
1
Order By: Relevance
“…However, for the hydroclimatic shift in 2014 no congruent changes in taxonomic and trait-based structures were found. The regimes and shifts in taxonomic and trait-based long-term variability, found in the study area, corresponded to shifts and changes, which were detected in the whole marine and North Sea ecosystem [49, 94, 95].…”
Section: Discussionmentioning
confidence: 92%
“…However, for the hydroclimatic shift in 2014 no congruent changes in taxonomic and trait-based structures were found. The regimes and shifts in taxonomic and trait-based long-term variability, found in the study area, corresponded to shifts and changes, which were detected in the whole marine and North Sea ecosystem [49, 94, 95].…”
Section: Discussionmentioning
confidence: 92%
“…This pattern has been previously observed in the macro-infauna at L4, with deposit feeders rapidly responding to phytodetrital input with an increase in abundance, while predators and scavengers responded more slowly with an increase in biomass (Zhang et al ., 2015). While many studies have concluded that benthic communities can be structured by phytodetrital input over both short-term and decadal scales (Buchanan, 1993; Josefson et al ., 1993; Dauwe et al ., 1998; Wieking & Kröncke, 2005; Frid et al ., 2009 a , 2009 b ; Clare et al ., 2017) clear responses to organic input from benthic fauna can be difficult to detect (Graf et al ., 1982; Reiss & Kröncke, 2004). The ‘food bank’ hypothesis suggests that large reserves of labile organic matter in sediments can sustain benthic communities at constant levels of abundance on a year round basis, and clear responses to phytodetrital input are difficult to detect as a consequence (Mincks et al ., 2005; Kędra et al ., 2012; Włodarska-Kowalczuk et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The trophic structure of North Sea macrofauna communities was found to reflect differences in the relative quality of organic matter received (Dauwe et al ., 1998; Wieking & Kröncke, 2005), and between 55% and 84% of year to year variability in benthic infaunal abundance off the coast of Northumberland was explained by changes in primary production (Buchanan, 1993). A marked increase in macrofaunal abundance in the same area in the 1980s was attributed to increases in phytodetrital input (Frid et al ., 1996), as were decadal-scale variations in taxonomic composition (Frid et al ., 2009 a , 2009 b ; Clare et al ., 2017). Josefson et al .…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative and qualitative changes in phytoplankton have unavoidable consequences at the other trophic levels. Several studies of benthic communities revealed that their diversity and function depended on the amount and quality of organic matter produced in the water column, even at extreme depths (Rowe and Pariente 1992;Clare et al 2017). The DFA's results of the Arctic HAUSGARTEN time-series (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) revealed strong relationships between the phytoplankton composition and concentrations of biogenic sediment compounds, indicating organic matter in surface sediments with the explanatory variables chosen for our analysis.…”
Section: Biological Responses To Crs and The Role Of Temperaturementioning
confidence: 99%